De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features. - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (Am J Hum Genet, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
Keywords: Acyltransferases; Arachidonic Acid; Autistic Disorder; Child; Child, Preschool; Consanguinity; Epilepsy; Female; Homozygote; Humans; Infant; Intellectual Disability; Lysophospholipids; Male; Membrane Proteins; Mutation; Pedigree; Phosphatidylinositols